1976
DOI: 10.1203/00006450-197607000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Transplacental Migration and Accumulation in Blood of Volatile Organic Constituents

Abstract: ExtractGas chromatographic-mass spectrometric analysis of profiles of low molecular weight volatile organic constituents obtained from cord blood and maternal blood samples collected at birth reflect transplacentally acquired compounds. The transplacental passage of halogenated hydrocarbons, plastic components, and abnormal accumulations of compounds have been demonstrated. I n the 11 paired cord blood-maternal blood samples analyzed, the relative amounts of constituents in cord blood closely correspond to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…The studies designed specifically to investigate developmental effects are limited, primarily because of concomitant exposure to other chemicals, inadequate sample size, and lack of quantification of exposure levels (Budnick, et al, 1984;Goldman, et al, 1985;Heath, 1983;Olsen, 1983). Benzene crosses the human placenta and is present in the cord blood in amounts equal to or greater than those in maternal blood (Dowty, et al, 1976). In a study of subjects with known benzene poisoning in Italy, Forni, et al (1971) reported the case of one pregnant worker exposed to benzene in the air during her entire pregnancy.…”
Section: Developmental Effectsmentioning
confidence: 98%
“…The studies designed specifically to investigate developmental effects are limited, primarily because of concomitant exposure to other chemicals, inadequate sample size, and lack of quantification of exposure levels (Budnick, et al, 1984;Goldman, et al, 1985;Heath, 1983;Olsen, 1983). Benzene crosses the human placenta and is present in the cord blood in amounts equal to or greater than those in maternal blood (Dowty, et al, 1976). In a study of subjects with known benzene poisoning in Italy, Forni, et al (1971) reported the case of one pregnant worker exposed to benzene in the air during her entire pregnancy.…”
Section: Developmental Effectsmentioning
confidence: 98%
“…The exposure is likely to occur from environmental tobacco smoke (Stjenfeldt et al 1986;Homann et al 1989;John et al 1991;Tredaniel et al 1994;Brondum et al 1999;Boetta et al 2000) and combustion emissions, particularly from automobiles (Paustenbach et al 1993;Nordlinder and Jarvholm 1997;Wol 1992). It has been reported that tissue concentrations of benzene in human fetuses of mothers exposed to the compound are comparable to or higher than those in the mothers (Dowty and Laseter 1976). However, not much is known about the health eects of the compound in the immature.…”
Section: Introductionmentioning
confidence: 93%
“…Using a mass-spectrometric method, Dowty, Laseter, and Storer (1976) demonstrated MIBK in human maternal blood samples collected immediately after delivery. The authors interpreted this finding as indicating the potential for MIBK to enter the umbilical cord and cross the placenta.…”
Section: Distributionmentioning
confidence: 99%